1998
DOI: 10.1021/jf9707952
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Grape Juices Inhibit the in Vitro Oxidation of Human Low-Density Lipoproteins

Abstract: This study was aimed at determining the antioxidant activity of commercial grape juices in inhibiting the copper-catalyzed oxidation of human low-density lipoproteins (LDL) in vitro and at relating this activity to the phenolic composition of the juices. This work also evaluated the effect of vitamin C on this antioxidant activity. When standardized to a total phenolic concentration of 10 μM gallic acid equivalents (GAE), samples of grape juices inhibited LDL oxidation from 62 to 75%. White grape juices inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
2
16

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 29 publications
10
78
2
16
Order By: Relevance
“…Frankel et al (1998) and Vinson et al (1999) reported that in grape juice, the antioxidant activity was similar to that found in red wines. Grape juice contains a higher content of glycosylated phenolic compounds than red wine which, according to Hollman et al (1995), are more easily absorbed than the respective aglicons.…”
Section: Antioxidant Activitysupporting
confidence: 55%
“…Frankel et al (1998) and Vinson et al (1999) reported that in grape juice, the antioxidant activity was similar to that found in red wines. Grape juice contains a higher content of glycosylated phenolic compounds than red wine which, according to Hollman et al (1995), are more easily absorbed than the respective aglicons.…”
Section: Antioxidant Activitysupporting
confidence: 55%
“…However, compared with other studies of 100% Concord grape juice the means were generally lower than those reported elsewhere: e.g. Frankel et al (1998) in Westfield, NY (318.2 and 443.7 mg/L); and Borges et al (2013) in Southern Brazil (548.8 mg/L). Many of the differences between this study and others are likely due to sample processing methods.…”
Section: Resultscontrasting
confidence: 72%
“…Pastrana-Bonilla et al [25] found a total concentration of phenolic compounds of about 2178.8, 374.6 and 23.8 mg/g GAE (gallic acid equivalent) in skin, seed and pulp, respectively. Grape skins are the main source of grape phenolic compounds changing their content with grape variety, soil composition, climate, geographic origin, cultivation practices or exposure to diseases, such as fungal infections and reactions occurring during storage [1,[26][27][28]. The total phenolic compounds content in grapes juices (400 to 3000 mg/L) depends on the grape variety, grape maturity, geographical origin and soil type, sunlight exposure, and many other factors [29], besides the grape juice processing technology, such as grape juice extraction, contact time between juice and the grape solid parts (skins and seeds), pressing, thermal and enzymatic treatments.…”
Section: General Introductionmentioning
confidence: 99%